2021
DOI: 10.1002/pds.5203
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of decision and timing of safety related labeling changes for new drugs approved both in Japan and the United States

Abstract: Purpose It is important to make the most up‐to‐date drug safety information available to the public in a timely manner so that health care professionals and patients can consider the information. The aim of the present study was to investigate the consistency and simultaneity of safety related updates in product labeling in Japan and the United States. Methods New safety label changes that were made for new drugs approved concurrently both in Japan and the United States in the recent 5 years were identified an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 11 publications
1
5
0
Order By: Relevance
“…This means that the regulatory authority in each country/region often makes decisions individually. Several studies have found low concordance of safety warnings between countries, 14,[30][31][32] which is consistent with the present result. The discrepancies maybe caused by differences in data source (e.g., domestic adverse event reports), events of interest, and action thresholds.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…This means that the regulatory authority in each country/region often makes decisions individually. Several studies have found low concordance of safety warnings between countries, 14,[30][31][32] which is consistent with the present result. The discrepancies maybe caused by differences in data source (e.g., domestic adverse event reports), events of interest, and action thresholds.…”
Section: Discussionsupporting
confidence: 92%
“…In these cases, precautions for the events had been listed in the non‐warning sections of the Japanese labeling at the time of approval. A previous study showed that domestic adverse event reports were associated with a significant difference in the timing of labeling change between Japan and the US 14 . In the cases of linagliptin and lenvatinib, accumulation of domestic adverse event reports provided the rationale for adding the precautions to the warning section of the Japanese labeling, 22,23 which might have affected the difference in the revision dates.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our group previously investigated the concordance in decision and timing of safety-related labeling changes after approval in Japan and the US and reported a low level of concordance between countries [ 22 ]. In the present study, we revealed that the inconsistency existed from the time of approval even in the cohort of drugs concurrently approved in both countries in the recent 7 years.…”
Section: Discussionmentioning
confidence: 99%